Determinants of Psychological Aspects Related to Nurses' Performance in Hospitals - Suryadi Jauhari; Sumijatun Sumijatun; Tina Rosa (Indonesian Journal of Global Health Research, 2025)
The productivity of nursing care at Bhayangkara Hospital Level III Banda Aceh is directly influenced by nurse performance. Many variables influence how nurses work. Factors related to nurse performance from a management perspective have been identified by various theories and previous studies. However, the psychological elements of nurses that influence their performance in providing nursing care are still less well-recognized, such as psychological capital and mental health (depression, anxiety, and stress). The purpose of this study was to identify the relationship between psychological capital, mental health, and characteristics with nurse performance at Bhayangkara Hospital Level III Banda Aceh. Quantitative research was conducted with a cross-sectional study design. A sample of 59 nurses was selected using the total sampling method. Data collection used the Psychological Capital Questionnaire (PCQ), DASS-21, and Six-D Scale of Nursing Performance. Data were analyzed descriptively and inferentially. The results showed that partially there was no relationship between age (P = 1.000), gender (P = 0.789), education (P = 0.187), employment status (P = 1.000), length of service (P = 0.187), hope (P = 0.272), resilience (P = 0.448), anxiety (P = 0.448) and depression (P = 0.448) with the performance of nurses at Bhayangkara Hospital Level III Banda Aceh. Furthermore, there was a relationship between self-efficacy (P = 0.0001), optimism (P = 0.002) and stress (P = 0.012) with the performance of nurses at Bhayangkara Hospital Level III Banda Aceh. Logistic regression analysis showed that self-efficacy (P = 0.002), optimism (P = 0.007), and stress (P = 0.039) were significant predictors related to nurse performance at Bhayangkara Hospital Level III Banda Aceh. Self-efficacy was the most dominant predictor related to nurse performance at Bhayangkara Hospital Level III Banda Aceh (OR: 8.857).